How Do Advanced Molecular Tests Compare to Routine Clinical Laboratory Evaluation of CSF in Meningoencephalitis? A Study in 10 Urban Emergency Departments Across the USA. (4th October 2017) - Merlin, Toby L; Chancey, Scott; Zheng, Yueli; Bowzard, Brad; Fischer, Leah; Parker, Todd; Pillai, Satish; Talan, David; Moran, Gregory; Krishnadasan, Anusha; Santibanez, Scott; ,
Abstract: Background: The EMERGE ncy ID Net Study Group is investigating whether advanced molecular tests (AMT) increase the detection of causative agents in the CSF of patients presenting with meningoencephalitis (ME). We report findings from a pilot study using AMT on 18 CSF samples from 10 US Urban Emergency Departments. The purpose of the pilot was to compare the performance of these four AMT to established clinical laboratory methods. Methods: We investigated four AMT: (1) BioFire FilmArray ME Panel targeting 14 causative agents; (2) an in-house target-directed next generation sequencing assay targeting 25 agents; (3) a microarray capable of detecting >2, 500 agents; and (4) deep metagenomic next generation sequencing. For targeted sequencing, loci from 12 DNA-based and 13 RNA-based pathogens were amplified from the extracts by multiplex PCR. All sequencing was performed on an Illumina MiSeq using 500 cycle v2 Reagent Kits. Reads from the targeted sequencing were aligned to the 25 specific reference target sequences using Bowtie2 while metagenomics reads were processed with the taxonomic sequence classifying software Kraken. For microarray analysis, Lawrence Livermore Microbial Detection Array v2 arrays were hybridized with Cy3-labeled DNA or cDNA. Scanned images of arrays were analyzed by CLiMax 3.1. Results: Eight CSF samples had results positive for well-established causes of ME from prior testing (Table). The pilot study demonstrated none of the four AMT detected all causative agents in the eight CSF samples known to have well-established causes of ME. BioFire and targeted sequencing performed best, both detecting 6/8, metagenomics deep sequencing detected 3/8, and microarray detected 1/8. Conclusion: Despite the sophistication of AMT, they cannot detect pathogens they do not target, that are present in small numbers, or that have been eliminated from the CSF by the immune response. Despite the theoretical potential for microarray and metagenomic sequencing to detect thousands of different agents, the agents probably must be present at high levels for detection. Disclosures: All authors: No reported disclosures.